2015
DOI: 10.4103/0976-7800.153625
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral retiform variant of sertoli leydig cell tumour of ovary: An uncommon tumor with review of literature

Abstract: Sertoli-leydig cell tumors are the uncommon sex-cord stromal tumors of the ovary. We report a case of 42-year-old female with retiform variant of sertoli-leydig cell tumour. She presented with the complaint of mass in abdomen for 7 years. Ultrasound revealed bilateral ovarian mass suggestive of malignancy. Bilateral salpingo-oopherectomy with surgical staging was done. The tumor was diagnosed as stage I retiform variant of sertoli-leydig cell tumor on histopathology and immunohistochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Our review of the literature revealed 29 previously published cases of bilateral ovarian SLCT (Tables 1 and 2) 14,19–42 ; two of these are included in this study (cases 2 and 3 in Table 1). Where possible, the articles and the photomicrographs were reviewed to try to determine the type of SLCT; this was sometimes difficult, given a paucity of pathological description and photomicrographs.…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the literature revealed 29 previously published cases of bilateral ovarian SLCT (Tables 1 and 2) 14,19–42 ; two of these are included in this study (cases 2 and 3 in Table 1). Where possible, the articles and the photomicrographs were reviewed to try to determine the type of SLCT; this was sometimes difficult, given a paucity of pathological description and photomicrographs.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 5 Most SLCTs were unilateral, and a tiny minority were bilateral. 7 , 8 Androgen overproduction always causes hirsutism, acne, deepening of the voice, breast atrophy, and clitorimegaly in SLCT patients. 2 In our study, patients showed irregular menstruation, hirsutism, acne, rougher voice, and breast development stagnation.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous components occur in nearly 20% of SLCTs, including gastric epithelium, retinal tissue, cartilage, or carcinoid tumors. 7 , 8 , 10 As a part of SLCTs, Leydig cells scatter among numerous Sertoli cells, arranging into open or closed tubules. Leydig cells are derived from the original mesenchyme of the mesonephros, and can produce and secrete testosterone, 11 making SLCTs functional ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in our cases, those tumors have usually unilateral localization; but in rare cases bilateral localizations have also been reported. 4,5 Clinical signs and symptoms comprising secondary amenorrhea and varying degrees of virilization are dependent on the testosterone produced by tumor cells. 6 Rare estrogenic findings may also be observed.…”
Section: Discussionmentioning
confidence: 99%